A descontinuidade em banco comercial privado nacional: um estudo de caso: o COMIND - Silva, José Rodrigues da (1990)
The purpose of this study is to identify and to describe the facts which indicate the causes of the discontinuity of the Banco Comércio e Indústria de são Paulo S.A. Commerce and Industry Bank of São Paulo - COMINO. On December 31st. 1974, COMINO assumed the position of the 6th in the ranking of the private banks in the country and on November 19th, 1985, it carne to be the biggest bank failure ever heard of in the whole history of banking in Brazil. The description will outline the course of its existence, with a particular emphasis on its last administration: We have tried to obtain consistent information concerning this case history by means of indirect documents, such as reports from Inquiry Commissions, audits and the Inquiry Commission of the Federal Chamber. The results we carne to permitted us to sequence the facts and proceed to a comparison with causes of bank failures which occurred mainly in the U.S.A. The conclusions of this research were based upon the evidence resulting from a comparative analysis, culminating with the comprehension that the bank administration was weak, inept, maladroit, and tending to centralize power, and that there was omission on the part of the independent auditor.